Implementasi Konsep Single Bar Dalam Organisasi Advokat Di Indonesia: Perspektif Ikatan Advokat Indonesia (IKADIN) - Herman Sitompul; Fitriyanti Fitriyanti (BULETIN ADALAH, 2026)
Advocate organizations play a significant role in improving professional quality, enforcing codes of ethics, and conducting supervision and development of advocates. Within the framework of the legal profession, the single bar concept represents an organizational model that centralizes the authority to regulate and manage the advocate profession under a single professional body. This concept is legally grounded in Law Number 18 of 2003 concerning Advocates, which served as the basis for the establishment of the Indonesian Advocates Association (PERADI) by the Indonesian Advocates Association (IKADIN) together with seven other advocate organizations as the sole advocate organization in Indonesia. However, institutional developments following the issuance of Supreme Court Decree Number 073/KMA/HK.01/IX/2015 have led to the emergence of various advocate organizations performing professional functions, thereby generating debates regarding the existence and implementation of the single bar system in Indonesia. This article aims to analyze the single bar concept within Indonesia's advocate organizational framework from the perspective of IKADIN and to examine the challenges faced in maintaining PERADI's position as the sole advocate organization. The study finds that the single bar concept continues to possess a strong juridical foundation under the Advocate Law; however, its implementation faces significant challenges arising from regulatory developments, judicial decisions, and the evolving dynamics of advocate organizations in Indonesia. Keywords: Single Bar, Advocate Organization, PERADI, IKADIN, Advocate Profession.